Theoretical Study on Two-Photon Absorption Properties of a Zinc Ion Probe Based on ICT Mechanism: Effects of Coordination Mode (Journal of Atomic and Molecular Sciences, 2018)
The one- and two-photon absorption, as well as the emission properties of a ratiometric zinc ion probe have been theoretically investigated employing the time-dependent density functional theory and response theory. Various coordination geometries have been considered. Special emphasis is placed on the effects of coordination mode on the optical properties. Our results demonstrate that upon combining with zinc ion, the one-photon absorption (OPA), emission and two-photon absorption (TPA) wavelengths show considerable red shift due to the enhanced internal charge transfer mechanism. Moreover, their intensities are enhanced to some extent. It is also shown that the red shifts are quite different for various coordination geometries. When the zinc ion is connected with the electron acceptor of the fluorophore, the OPA, emission and TPA wavelengths have larger red shifts induced by the lower energy gaps between the related molecular orbitals.